RUANG PUBLIK DAN AGENSI PEREMPUAN DALAM DIALOG ANTARAGAMA: : Pendekatan Feminis Sosiokultural di Palangka Raya - Sharon Michelle O. Pattiasina; Jinny Ningsih; Angel Keristina (Institut Agama Kristen Negeri Toraja, 2026)
Abstract: This study aims to analyze the role of women in public spaces as agents of interfaith dialogue in Palangka Raya through a sociocultural feminist perspective. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through observation, in-depth interviews, and documentation involving women entrepreneurs, artists, representatives of the Department of Industry and Trade (Disperindag), and the Regional National Crafts Council (Dekranasda) of Palangka Raya. The analysis draws upon Habermas’s theory of the public sphere, Arendt’s concept of the space of appearance, Honneth’s theory of recognition, and sociocultural feminist perspectives emphasizing women’s agency within social and cultural relations. The findings reveal that public spaces in Palangka Raya function as arenas of social recognition, empowerment, and identity formation for women. Through participation in economic, cultural, artistic, and interfaith social activities, women develop interfaith dialogue through three models: parliament of religions dialogue, activism-based dialogue, and storytelling dialogue. The study further finds that Dayak local wisdom values, including handep (mutual cooperation), hapakat (consensus), and huma betang (communal living), strengthen inclusive and participatory interfaith relations. Despite encountering patriarchal constraints, women exercise transformative agency through social negotiation, collaboration, and cross-faith solidarity, contributing significantly to social cohesion within a multicultural and multireligious society. Abstrak: Tulisan ini bertujuan untuk menganalisis peran perempuan dalam ruang publik melalui praktik dialog antaragama di Kota Palangka Raya dengan menggunakan pendekatan perspektif feminis sosiokultural. Penelitian menggunakan metode kualitatif dengan pendekatan sosiologi agama. Teknik pengumpulan data yang digunakan ialah observasi, wawancara, dan dokumentasi terhadap pelaku UMKM khususnya kaum perempuan, seniman, perwakilan Dinas Perindustrian dan Perdagangan Kota Palangka Raya, dan Dewan Kerajinan Nasional Daerah Kota Palangka Raya. Hasil penelitian menunjukkan bahwa ruang publik di Palangka Raya berfungsi sebagai arena eksistensi, pengakuan sosial, dan pemberdayaan perempuan. Dalam hal ini, melalui keterlibatan pada kegiatan ekonomi, seni, budaya, dan sosial lintas agama, kaum perempuan membangun praktik dialog antaragama dalam bentuk dialog berbasis aktivisme dan dialog yang berlangsung melalui storytelling. Penelitian ini juga menemukan bahwa nilai-nilai kearifan lokal seperti Handep, Hapakat, dan Huma Betang menjadi landasan dalam proses dialog antaragama yang inklusif dan partisipatif. Meskipun menghadapi hambatan patriarkal, perempuan mampu mengembangkan agensi transformasi melalui proses negosiasi sosial, kolaborasi, dan solidaritas lintas iman yang memperkuat kohesi sosial dalam masyarakat multireligius.